Keiserlik-kuningliku armee mitmekesistest vormipükstest (1867–1918). Sõjaväeline ühtlustamine ja territoriaalse koostöö võimalused [On the Diversity of Pants in the Imperial and Royal Army (1867–1918). Dichotomy of Regional Traditions and State Centralism] - Tšoli, Sergi (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2018)
This article deals with the process of army reformation during the late Habsburg Monarchy and discusses the role of local military privileges in the state structure, governance and territorial cooperation of the Empire.The late Habsburg Monarchy was a country of permanent modernization that could easily be traced in many aspects of life, the military among them. Starting in 1868, the Habsburgs applied universal conscription for their army and began a long-term programme of reformation and improvement in their armed forces. Th e main architect of the programme was archduke Albrecht and his main ideas were realized in the army until 1914. Among the most important components of the military reform was following the unifi cation and centralization of the army, cancellation of local military privileges and creation of a single governing body for all the soldiers of the Empire – k. u. k. Ministry of War in Vienna. At the same time, we could see that even after 1868 there were several territories with local military privileges at diff erent levels. The main task of this article is to discuss the real role of such privileges in the imperial military structure and fi gure out the main reasons for their existence, often in contradiction to the centralistic attempts of the Empire. By 1914, the Habsburgs cancelled the military privileges of Fiume, Catarro, Trieste, Dalmatia and Military Frontier, but at the same time kept them for Tirol and Vorarlberg, Bosnia and Herzegovina, Croatia and Slavonia to say nothing of Hungary. In each case there the Habsburgs had their own reasons why they refused to unify the whole military system of the Monarchy and retained military autonomy for some territories. At the same time, this situation brought to life diff erent forms of cohesion and coherence at diff erent levels – from community self-defence organizations in Tirol and Vorarlberg to the Ministry of Territorial Defence and Territorial Army (Honvéd) in Hungary.The realities of the Great War demonstrated further development of the above listed processes, when on the one hand, the army was very much unifi ed in its organization and governing structure, on the other, the separate administrative status of Hungary gave it the right to discuss its role in the war and oppose attempts by Vienna to mobilize huge military contingents for the front.